Culture and Cross-Cultural Understanding: A Panacea for Peaceful Coexistence among Ethnic Groups in Nigeria. - Folorunso, Paul Olorunsola (NIU Journal of Social Sciences, 2018)
Culture is a human legacy bequeathed through interaction with nature. It is the capacity of man to express and act within specific environmental contingencies and also the totality of man represented in the phenomena of knowledge, arts, morals, law, and custom as acquired by man in his society. On the other hand peaceful coexistence is a desirable human experience, an inescapable fact situated at the fulcrum of man’s survival in the universe. Hence, Nigeria as a nation is a culturally diverse society whose history had witnessed lots of uprising from ethnic disagreements and rivalries even up till the present time. This paper not only sets out to show periodization of ethnic conflicts in Nigeria nor entertain the most celebrated evidences to back up the debates about universalism and relativism in cultural polemics about the nation called Nigeria, but to argue how cross-cultural understanding can veritably bridge the perceived lacuna and tension arising from cultural differences. The paper notes that cross-cultural understanding is open-minded and seeks an understanding of relation that sees the world from others perspectives. It is also an understanding that is dialectic, self-reflexive and able to engage and integrate positive and progressive aspects of cultures for a harmonious peaceful co-existence of all the ethnic groups in Nigeria. Keywords : Culture, Cross-cultural Understanding, Peaceful Co-existence